Renal function in Ankylosing Spondylitis - Renu Saigal; Arun Kumar Agrawal; Laxmikant Goyal; Abhishek Agrawal; Naveen Gupta (Indian Journal of Rheumatology)
Background: To study renal functions in patients with ankylosing spondylitis (AS) and compare with matched healthy controls and correlation between renal function parameters and disease activity markers. Methods: Renal functions of forty cases with AS and the same number of age- and sex-matched individuals were evaluated. Disease activity was assessed using Bath Ankylosing Spondylitis Disease Activity Index, Bath Ankylosing Spondylitis Functional Index, Bath Ankylosing Spondylitis Metrology Index scores, C-reactive protein, and erythrocyte sedimentation rate. Results: Among AS cases, 31 AS cases (77.50%) had renal function abnormalities including hematuria (20%), proteinuria (30%), albuminuria (52.50%), increased 24 h urine protein (22%), raised serum creatinine (17%), and reduced glomerular filtration rate (GFR) (37%). Among healthy controls, 20/40 (50%) had renal function abnormalities including albuminuria (15%), raised serum creatinine (7.50%), and reduced GFR (20%). Abnormal renal functions were significantly more in AS cases (31/40, 77%) than healthy controls (20/40, 50%) (P < 0.05). Renal function abnormalities were more frequent among AS cases having elevated markers of disease activity. Renal abnormalities were more prevalent in cases taking nonsteroidal anti-inflammatory drugs (NSAIDs) for < 48 months than cases taking these drugs for ≥48 months, suggesting that these renal abnormalities were probably not due to NSAIDs-induced nephropathy but may be due to AS itself. Conclusions: In this study with small number of participants abnormalities in the renal function were common in patients with AS. No significant correlation was found between renal functions and markers of disease activity.